On graph-based design of floor layouts - Borkowski, Adam; Chaś, Grzegorz; Nguyen, Quoc Thanh (Journal of Civil Engineering and Management, 2003)
Knowledge-based tools assisting the designer in engineering represent further improvement of expert systems. The present paper shows how such software can be developed in the particular domain of floor layout design for buildings. The recently developed paradigm of hierarchical graphs is taken as the knowledge representation scheme. The user of the system is encouraged to undertake the search for rational solution at two levels. First, an analysis of functionality requirements for the designed object is performed. This results in a graph capturing main functions and relations between them. Further, this graph is mapped onto another graph depicting the floor layout in terms of areas and rooms. Both graphs produced by the user are checked against the constraints resulting from the requirements of the relevant code of practice. The final result is converted into the format accepted by a commercial CAD-tool in order to proceed with the detailed design.First Published Online: 26 Jul 2012